From Function to Metabolome: Metabolomic Analysis Reveals the Effect of Probiotic Fermentation on the Chemical Compositions and Biological Activities of Perilla frutescens Leaves - Wang, Zhenxing; Jin, Ximeng; Zhang, Xuechun; Xie, Xing; Tu, Zongcai; He, Xiahong (Frontiers in Nutrition, 2022)
In this study, Perilla frutescens leave (PFL) was fermented for 7 days using six probiotics, which were Lactobacillus Plantarum SWFU D16, Lactobacillus Plantarum ATCC 8014, Lactobacillus Rhamnosus ATCC 53013, Streptococcus Thermophilus CICC 6038, Lactobacillus Casei ATCC 334, Lactobacillus Bulgaricus CICC 6045, respectively. Then, the active components and functional activity of PFL during the fermentation process were evaluated, including the total phenol content, total flavonoid content, antioxidant abilities, α-glucosidase inhibition ability, and acetylcholinesterase inhibition ability. High-performance liquid chromatography was further carried out to quantify its bioactive compounds. Finally, non-targeted ultra-high-performance liquid chromatography-tandem mass spectroscopy was used to identify the metabolites affected by fermentation and explore the possible mechanism of action of fermentation. The results showed that noticeable variations in the active component contents and functional activities of PFL were observed during the fermentation process, most of which exhibited that first increased and then decreased, and different probiotics had clearly distinguishable effects from each other. The same trend was also confirmed by the HPLC analysis result of the changes in the contents of 12 phenolic acids and flavonoids. It was found that fermentation with ATCC 53013 for one day showed the highest enhancement effect. Under this fermentation condition, the further metabolomic analysis revealed significant changes in metabolites during fermentation, which involved primarily the generation of fatty acids and their conjugates, flavonoids. A total of 574 and 387 metabolites were identified in positive ion and negative ion modes, respectively. Results of Spearman’s analysis indicated that some primary metabolites and secondary metabolites such as flavonoids, phenols, and fatty acids might play an important role in the functional activity of PFL. Differential metabolites were subjected to the KEGG database and obtained 97 metabolites pathways, of which biosynthesis of unsaturated fatty acids, flavonoid biosynthesis, and isoflavonoid biosynthesis were the most enriched pathways. The above results revealed the potential reason for the differences in metabolic and functional levels of PFL after fermentation. This study could provide a scientific basis for the further study of PFL, as well as novel insights into the action mechanism of probiotic fermentation on the chemical composition and biological activity of food/drug.